맥파를 이용한 사상체질의 진단에 있어서 분류방법에 따른 진단의 정확도 비교 - 신상훈(Sang-Hoon Shin); 김종열(Jong-Yeol Kim) (한국콘텐츠학회 논문지, 9(10), 2009)
The purpose of this study is to find a classification method with high accuracy in regard with sasang constitutional diagnosis. The BMI, blood pressure, pulse wave, and Sasang constitution diagnosed by a specialist was collected from 2848 subjects who were apparently healthy. Through a selective procedure, the data of 1635 subjects was used in the analysis. The results with the classification methods such as the discriminant analysis, regression, decision tree and neural network were compared with the diagnosis of a Sasang constitutional specialist. In result, the discriminant analysis method was hard to qualify the assumption of the equality of covariance matrices within constitutional groups. Moreover, without BMI, the decision tree and neural network methods were very sensitive to the change of the analysis data. Therefore, the Logistic regression and the decision tree is recommended on condition that the decisive factors of constitution are well concerned. 사상의학은 체질에 따라 치료하는 방법을 달리하므로, 체질진단의 객관화가 절실히 요구되고 있다. 본 연구는 맥파를 이용하여 사상체질을 객관적으로 진단함에 있어서, 정확도가 높으면서 실용적인 체질분류 방법을 탐색하는 것이 목적이다. 한방병원에 건강검진을 목적으로 내원한 2848명의 피험자를 대상으로 전문의가 진단한 체질, 체질량지수, 혈압, 맥파 자료를 입수하였다. 자료의 선별과정을 통하여 최종적으로 1635명의 자료를 분석에 사용하였다. 판별분석, 회귀분석, 의사결정나무, 신경망으로 체질을 예측하고 전문의가 진단한 결과와 비교하여 분류방법의 정확도를 비교하였다. 판별분석은 체질별로 공분산 행렬이 동일해야 한다는 가정을 만족시키기 어려웠으며, 체질량지수를 고려하지 않은 의사결정나무와 신경망 분석의 결과는 분석표본의 변동에 민감했다. 체질분류에 결정적인 영향을 미치는 변수인 체질량지수가 고려된 로지스틱 회귀분석 또는 의사결정나무 방법이 체질분류 방법으로 추천할 만하다.